PENGEMBANGAN ANALISIS KONSUMSI ENERGI LISTRIK MENGGUNAKAN METODE DISAGREGASI - Sinaga, Elsanita
World energy consumption rises and is predicted to increase up to 28% in 2040. Unfortunately, the increasing energy demand is not balanced with energy avaibility. To make the energy avaibility and energy demand balanced, savings through energy management needs to be done. This study propose an energy management by electrical energy consumption analysis using energy disaggregation. This research take advantage of the Internet of Things concept in communicate, storange and data analytics. Load activity simulation has been done using four bulbs with different usage power. After that, appliance characterization was carried out and the algoritm was applied to detect the activation of three equipment in kitchen. From the experiment, the algoritm can detect the load activity by four bulbs with acuracy 100% and 78% when it is applied to household appliance. After that 1D and 2D clustering method had been done to detect the multistate. By using this method, it is obtained an acuracy about 100% for 1D and 90% for 2D.